Please show all of the steps to solve the Algebra math problems below.Evaluate the following.|10| = |-4| =Subtract. Write your answer as a fraction in simplest form.5/8 � 3/8 =Subtract.7/8 � 5/6Write your answer as a fraction in simplest form.Multiply.6*(-7/2) =Write your answer in simplest form.Divide. Write your answer as a fraction or mixed number in simplest form.6/5 / (- 12/25) =Evaluate.3 + 4^2 * 2 =Evaluate.2/3 + 5/6 * � =Write your answer in simplest form.Evaluate-16 - 12 / (-4) =Use the distributive property to remove the parentheses.-9(3w � x � 2) =Simplify.-2(w + 2) + 5w =Simplify the following expression.16x^2 + 8 � 10x � 2x^2 � 14x =Evaluate the expression when b = -5 and y = 6b � 9y =Evaluate the expression when y = -3Y^2 + 5y � 4 =Evaluate.(-4)^3 =(-7)^2 =Evaluate. Write your answers as fractions.3/5^3 =(-1/3)^2 =Evaluate the expressions.(-7)^0 =2(1/3)^0 = Multiply.3v^2(-5v^4) =Simplify your answer as much as possible.Multiply.2y^2w^4*6y*2w^8 =Simplify your answer as much as possible.Simplify.(4p^3/3p^7)^-2 =Write your answer using only positive exponents.Simplify.X^-2/x^-3 =Write your answer with a positive exponent only.

Respuesta :

Answer:

See Explanation

Step-by-step explanation:

Please note that I'll replace all � with +

1. |10|

This implies the absolute value of 10 and it always returns the positive value;

Hence;

[tex]|10| = 10[/tex]

2. |-4|

Using the same law applied in (1)

[tex]|-4| = 4[/tex]

3.  5/8 - 3/8 = ?

Take LCM

[tex]= \frac{5 - 3}{8}[/tex]

Subtract the numerator

[tex]= \frac{2}{8}[/tex]

Divide the numerator and denominator by 2

[tex]= \frac{1}{4}[/tex]

Hence:

[tex]\frac{5}{8} - \frac{3}{8} = \frac{1}{4}[/tex]

4. 7/8 - 5/6

Take LCM

[tex]= \frac{21 - 20}{24}[/tex]

[tex]= \frac{1}{24}[/tex]

Hence;

[tex]\frac{7}{8} - \frac{5}{6} = \frac{1}{24}[/tex]

5. 6 * (-7/2)

[tex]= 6 * \frac{-7}{2}[/tex]

Multiply the numerator

[tex]= \frac{-42}{2}[/tex]

[tex]= -21[/tex]

Hence:

[tex]6 * \frac{-7}{2} = -21[/tex]

5. 6/5 /(-12/25)

[tex]= \frac{6}{5} / \frac{-12}{25}[/tex]

Change the divide to multiplication

[tex]= \frac{6}{5} * \frac{-25}{12}[/tex]

Divide 6 and 12 by 6

[tex]= \frac{1}{5} * \frac{-25}{2}[/tex]

Divide 5 and 25 by 5

[tex]= \frac{1}{1} * \frac{-5}{2}[/tex]

[tex]= \frac{-5}{2}[/tex]

Hence;

[tex]\frac{6}{5} / \frac{-12}{25} = \frac{-5}{2}[/tex]

6.  3 + 4^2  * 2

[tex]= 3 + 4^2 * 2[/tex]

Solve the exponent

[tex]= 3 + 16 * 2[/tex]

Apply B.O.D.M.A.S

[tex]= 3 + 32[/tex]

[tex]= 35[/tex]

[tex]3 + 4^2 * 2 = 35[/tex]

7.  2/3 + 5/6

[tex]= \frac{2}{3} + \frac{5}{6}[/tex]

Apply LCM

[tex]= \frac{4 + 5}{6}[/tex]

[tex]= \frac{9}{6}[/tex]

Divide the numerator and denominator by 3

[tex]= \frac{3}{2}[/tex]

Convert to mixed fraction

[tex]= 1\frac{1}{2}[/tex]

Hence;

[tex]\frac{2}{3} + \frac{5}{6} = 1\frac{1}{2}[/tex]

8.  16 - 12/(-4)

[tex]= 16 - \frac{12}{-4}[/tex]

Solve the fraction

[tex]= 16 - (-3)[/tex]

Open the bracket

[tex]= 16 + 3[/tex]

[tex]= 19[/tex]

Hence;

[tex]16 - \frac{12}{-4} = 19[/tex]

9.   -9(3w + x + 2)

[tex]= -9(3w + x + 2)[/tex]

Open brackets: Distributive property

[tex]= -9*3w -9* x -9 * 2[/tex]

[tex]= -27w -9 x -18[/tex]

Hence;

[tex]-9(3w + x + 2) = -27w -9 x -18[/tex]

10.  -2(w + 2) + 5w

[tex]= -2(w + 2) + 5w[/tex]

Open bracket: using distributive property

[tex]= -2*w -2 * 2 + 5w[/tex]

[tex]= -2w -4 + 5w[/tex]

Collect Like Terms

[tex]= 5w-2w -4[/tex]

[tex]= 3w -4[/tex]

Hence;

[tex]-2(w + 2) + 5w = 3w- 4[/tex]

11.   16x^2 + 8 + 10x + 2x^2 + 14x

[tex]= 16x^2 + 8 + 10x + 2x^2 + 14x[/tex]

Collect Like Terms

[tex]= 16x^2 + 2x^2 + 10x + 14x+ 8[/tex]

[tex]= 18x^2 + 24x + 8[/tex]

Expand the expression

[tex]= 18x^2 + 12x + 12x + 8[/tex]

Factorize:

[tex]= 6x(3x + 2) + 4(3x +2)[/tex]

[tex]= (6x + 4)(3x +2)[/tex]

Hence;

[tex]16x^2 + 8 + 10x + 2x^2 + 14x = (6x + 4)(3x +2)[/tex]

12. b = -5 and y = 6

[tex]b + 9y =?[/tex]

Substitute -5 for b and 6 for y

[tex]= -5 + 9 * 6[/tex]

[tex]= -5 + 54[/tex]

[tex]= 49[/tex]

Hence;

[tex]b + 9y = 49[/tex]

13.    y = -3

[tex]y^2 + 5y + 4 =?[/tex]

Substitute -3 for y

[tex]= (-3)^2 + 5(-3) + 4[/tex]

Open all brackets

[tex]= 9 -15 + 4[/tex]

[tex]= -2[/tex]

Hence;

[tex]y^2 + 5y + 4 = -2[/tex]

14.  

[tex](-4)^3[/tex]

Open bracket:

[tex]= -4 * -4 * -4[/tex]

[tex]= -64[/tex]

Hence;

[tex](-4)^3 = -64[/tex]

[tex](-7)^2[/tex]

Open bracket:

[tex]= -7 * -7[/tex]

[tex]= 49[/tex]

Hence;

[tex](-7)^2 = 49[/tex]

15.  Express as fractions:

[tex]\frac{3}{5^3}[/tex]

Evaluate the denominator

[tex]= \frac{3}{125}[/tex]

Hence:

[tex]\frac{3}{5^3} = \frac{3}{125}[/tex]

[tex](\frac{-1}{3})^2[/tex]

Evaluate the exponent

[tex]= (\frac{-1}{3})*(\frac{-1}{3})[/tex]

[tex]=\frac{1}{9}[/tex]

Hence:

[tex](\frac{-1}{3})^2=\frac{1}{9}[/tex]

16. Evaluate

[tex](-7)^0 =[/tex]

Evaluate the exponent

[tex](-7)^0 = 1[/tex]

[tex]2 * (1/3)^0[/tex]

Evaluate the exponent

[tex]= 2 * 1[/tex]

[tex]= 2[/tex]

Hence;

[tex]2 * (1/3)^0 = 2[/tex]

17. Evaluate

[tex]3v^2(-5v^4)[/tex]

Open bracket

[tex]= 3 * v^2*-5* v^4[/tex]

Reorder

[tex]= 3 *-5* v^4 * v^2[/tex]

[tex]= -15* v^4 * v^2[/tex]

Apply law of indices

[tex]= -15* v^{4 +2}[/tex]

[tex]= -15* v^6[/tex]

[tex]= -15v^6[/tex]

Hence:

[tex]3v^2(-5v^4) = -15v^6[/tex]

18.

[tex]2y^2w^4*6y*2w^8[/tex]

Rewrite as

[tex]2 *y^2 * w^4*6 * y*2 * w^8[/tex]

Reorder the terms

[tex]=2*6 * w^4 * w^8*y^2 * y*2[/tex]

[tex]=12 * w^4 * w^8*y^2 * y*2[/tex]

Apply law of indices

[tex]=12 * w^{4+8} *y^{2+2}[/tex]

[tex]=12 * w^{12} *y^4[/tex]

[tex]=12 w^{12} y^4[/tex]

Hence:

[tex]2y^2w^4*6y*2w^8 =12 w^{12} y^4[/tex]

19.

[tex](\frac{4p^3}{3p^7})^{-2}[/tex]

Apply law of indices

[tex]= (\frac{4p^{3-7}}{3})^{-2}[/tex]

[tex]= (\frac{4p^{-4}}{3})^{-2}[/tex]

Apply law of indices

[tex]= (\frac{4}{3p^4})^{-2}[/tex]

Apply law of indices

[tex]= (\frac{3p^4}{4})^{2}[/tex]

[tex]= (\frac{3p^4}{4}) * (\frac{3p^4}{4})[/tex]

Evaluate

[tex]= \frac{9p^8}{16}[/tex]

Hence;

[tex](\frac{4p^3}{3p^7})^{-2} = \frac{9p^8}{16}[/tex]

20.

[tex]\frac{x^{-2}}{x^{-3}}[/tex]

Apply law of indices

[tex]= x^{-2 - (-3)}[/tex]

[tex]= x^{-2 +3}[/tex]

[tex]= x^1[/tex]

[tex]= x[/tex]

Hence:

[tex]\frac{x^{-2}}{x^{-3}} =x[/tex]